Remarkable flux effect of Li-codoping on highly enhanced luminescence of orthosilicate Ba2SiO4:Eu2+ phosphors for NUV-LEDs: autonomous impurity purification by eutectic Li2CO3 melts. Issue 127 (14th December 2015) - Kim, Donghyeon; Jeon, Ki-Wan; Jin, Jong Sung; Kang, Seong-Gu; Seo, Dong-Kyun; Park, Jung-Chul
Abstract : The PL intensity of Li-doped Ba2 SiO4 :Eu 2+ (Li = 200% excess) is found to be 470% higher than that of Ba2 SiO4 :Eu 2+ (no-Li). The excess Li2 CO3 autonomously removes the impurities contained in the low-purity precursors, in particular SiO2 . Abstract : We report large photoluminescence (PL) enhancement of green-emitting Ba2 SiO4 :Eu 2+ phosphors prepared in an eutectic Li2 CO3 melt as a flux. Among the phosphor materials synthesized using low-purity precursors (99%-pure BaCO3 and 99.6%-pure SiO2 ), the emission intensity of Ba2 SiO4 :(Li0.02, Eu0.02 ) (Li = 200% excess) is found to be 470% as high as that of Ba2 SiO4 :Eu0.02 (no-Li) and in fact is almost equivalent to that of Li-undoped Ba2 SiO4 :Eu 2+ synthesized using ultrapure precursors (99.98%-pure BaCO3 and 99.995%-pure SiO2 ). In combination with the results from PL measurements and inductively coupled plasma mass spectrometry (ICP-MS), the elemental distribution of the products and melts found from time-of-flight secondary ion mass spectrometry (TOF-SIMS) directly indicates that the excess Li2 CO3 autonomously removes the impurities that were originally contained in the low-purity precursors, in particular SiO2, and thus critically improves the photoluminescence efficiency of the material. The newly found Li flux effect on large PL enhancement may not only contribute to more economic production of phosphors but provide a platform for discovery of new efficient phosphors for solid state lighting.